ЕМОЦІЇ В СИСТЕМІ МИСЛЕННЄВОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2009)
The article deals with different aspects of intellectual activities from the viewpoint of A. Leontiev's psychological theory of activities. The main point of "unity of an affect and an intellect" problem is revealed.